Public Health Implications of Changing Rodent Importation Patterns – United States, 1999–2013. Issue 2 (5th August 2015) - Lankau, E. W.; Sinclair, J. R.; Schroeder, B. A.; Galland, G. G.; Marano, N.
Summary: The United States imports a large volume of live wild and domestic animal species; these animals pose a demonstrated risk for introduction of zoonotic diseases. Rodents are imported for multiple purposes, including scientific research, zoo exhibits and the pet trade. Current U.S. public health regulatory restrictions specific to rodent importation pertain only to those of African origin. To understand the impacts of these regulations and the potential public health risks of international rodent trade to the United States, we evaluated live rodent import records during 1999–2013 by shipment volume and geographic origin, source (e.g. wild‐caught versus captive‐ or commercially bred), intended purpose and rodent taxonomy. Live rodent imports increased from 2737 animals during 1999 to 173 761 animals during 2013. Increases in both the number and size of shipments contributed to this trend. The proportion of wild‐captured imports declined from 75% during 1999 to <1% during 2013. Nearly all shipments during these years were imported for commercial purposes. Imports from Europe and other countries in North America experienced notable increases in volume. Gerbils and hamsters arriving from Europe and chinchillas, guinea pigs and hamsters arriving from other countries in North America were predominant taxa underlying this trend. After 2003, African‐origin imports became sporadic events under the federal permit process. These patterns suggest development of large‐scale captive rodent breeding markets abroad for commercial sale in the United States. While the shift from wild‐captured imports alleviates many conservation concerns and risks for novel disease emergence, such consolidated sourcing might elevate exposure risks for zoonotic diseases associated with high‐density rodent breeding (e.g. lymphocytic choriomeningitis or salmonellosis). A responsive border health system must periodically re‐evaluate importation regulations in conjunction with key stakeholders to ensure a balance between the economic benefits of rodent trade against the potential public health risks.